The effect of the numbered heads together cooperative learning model on students’ mathematical understanding in statistic - Wahyuni, Dewi Sri; Sucipto, Lalu; Negara, Habibi Ratu Perwira (Journal of Didactic Mathematics, 2025)
Students' low understanding of mathematics is one of the main challenges in the learning process at school. This low understanding is often closely related to the learning methods used by teachers, which are less able to facilitate active involvement and deep understanding of concepts by students. This study aims to analyze the differences in mathematical comprehension abilities between students who learn through the Numbered Heads Together (NHT) cooperative model and conventional learning, and to examine the extent of the influence of the NHT model on students' mathematical comprehension abilities in the experimental class.This study used a quantitative approach with a quasi-experimental method and a nonequivalent pretest-posttest control group design. The population of the study was eighth grade junior high school students, with a cluster random sampling technique. The main instrument was a mathematical comprehension ability test, and the data were analyzed using normality, homogeneity, N-gain, t-test, and paired sample t-test.  The results of the study indicate that the Numbered Heads Together (NHT) learning model is more effective in enhancing students' mathematical understanding ability compared to conventional learning.